New Freshwater Sponges From Amazoniad Waters - Ribeiro, Cecilia Volker; Marciel, S . Becker (Amazoniana, 1983)
Four species of freshwater sponges have theu fust register of occurrence for Amazonian waters upon specimens collected from Culuene and Sete de Setembro Rivers (Xigú basin), Tapuapés River (Araguaia basin) and Cuieiras River. Trochospongilla pennsylvanica (POTTS 1882) and Trochospongilla vanabilis
Keywords: Trochospongilla Variabilis